2019
DOI: 10.7567/1347-4065/ab0342
|View full text |Cite
|
Sign up to set email alerts
|

Gibbs–Thomson effect on aluminum doping during trench-filling epitaxial growth of 4H-SiC

Abstract: Diffusion equations were solved to examine how the aluminum concentration in 4H-SiC grown on a trenched substrate is influenced by the Gibbs −Thomson (GT) effect. The GT effect increases or decreases the equilibrium gas-phase concentration of growing species in the vicinity of the top or bottom of the trench, respectively, which results in a part of the incident growing species, excluding the central area of the trench, diffusing inward. After fitting activity coefficient of a conditional constituent AlC in so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…By fitting the standard molar Gibbs free energy (G Al °= −500 kJ mol −1 ), 16) Segal et al reproduced the reported dependences of x in Al x Si 1-x C on growth temperature T g , total pressure, TMA flow rate, and R g 18) up to x = 0.01. 15) This quasi-thermodynamic model has also been used to quantitatively analyze aluminum doping during trench-filling epitaxial growth of 4H-SiC.…”
mentioning
confidence: 85%
See 4 more Smart Citations
“…By fitting the standard molar Gibbs free energy (G Al °= −500 kJ mol −1 ), 16) Segal et al reproduced the reported dependences of x in Al x Si 1-x C on growth temperature T g , total pressure, TMA flow rate, and R g 18) up to x = 0.01. 15) This quasi-thermodynamic model has also been used to quantitatively analyze aluminum doping during trench-filling epitaxial growth of 4H-SiC.…”
mentioning
confidence: 85%
“…15) This quasi-thermodynamic model has also been used to quantitatively analyze aluminum doping during trench-filling epitaxial growth of 4H-SiC. 16,19) The maximum x analyzed in this study is 5.8 × 10 -5 , 20) which is much less than 0.01. 15) Accordingly, the same model is employed to quantitatively analyze the reported x in Al x Si 1-x C on misoriented (0001) substrates.…”
mentioning
confidence: 94%
See 3 more Smart Citations